Menyelami Kebaikan Hati: Pentingnya Zakat dalam Merangkul Keadilan Sosial dalam Islam - Puji Chairunisa; Fretty Luciana Gurning; Dies L Tobing; Syuratty Astuti Rahayu Manalu (Sharia Journal and Education Center Publishing, 2023)
AbstractThis study focuses on the role of zakat in promoting social justice in Islamic societies. The research analyzes the theological, philanthropic, and economic aspects of zakat to understand how it contributes to community empowerment and poverty alleviation. The theological study explores how zakat reflects Islamic teachings on benevolence and generosity. The philanthropic analysis emphasizes zakat as a means of providing social services and creating positive social change. The economic aspect examines how zakat affects wealth distribution and aims to identify mechanisms that alleviate poverty. By taking a multidimensional approach, the study aims to provide a comprehensive understanding of zakat's contribution to building a just and equitable society. Ultimately, this research can offer insight into addressing social and economic inequalities within Muslim communities.Keywords: Zakat, Islamic Law, Distribution AbstrakPenelitian ini berfokus pada peran zakat dalam mempromosikan keadilan sosial dalam masyarakat Islam. Penelitian ini menganalisis aspek teologis, filantropis, dan ekonomi dari zakat untuk memahami bagaimana zakat berkontribusi terhadap pemberdayaan masyarakat dan pengentasan kemiskinan. Studi teologis mengeksplorasi bagaimana zakat mencerminkan ajaran Islam tentang kebajikan dan kedermawanan. Analisis filantropis menekankan zakat sebagai sarana untuk menyediakan layanan sosial dan menciptakan perubahan sosial yang positif. Aspek ekonomi mengkaji bagaimana zakat mempengaruhi distribusi kekayaan dan bertujuan untuk mengidentifikasi mekanisme yang dapat mengentaskan kemiskinan. Dengan menggunakan pendekatan multidimensi, penelitian ini bertujuan untuk memberikan pemahaman yang komprehensif mengenai kontribusi zakat dalam membangun masyarakat yang adil dan merata. Pada akhirnya, penelitian ini dapat memberikan masukan untuk mengatasi kesenjangan sosial dan ekonomi di masyarakat Muslim. Kata Kunci: Zakat, Hukum Islam, Distribusi